KAPASITAS KELEMBAGAAN MAJELIS RAKYAT PAPUA (MRP) Sebagai Lembaga Representatif Kultural Orang Asli Papua - , Terianus Luther Safkaur; , Dr. Erwan Agus Purwanto, M.Si, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
LawNo. 21 of2001 on Special Autonomy for Papua is a policy that is strategic, in order to improveservices, acceleration of development, and community empowennent in the province of Papua,especially the indigenous people of Papua. Through this policy is expected to reduce the gap between Papua province with other provinces within the framework of the Unitary Republic of Indonesia, and will provide opportunities for indigenous people of Papua to participateas subjects of development. MRP is a cultural representative of the indigenous Papuans,who have specific authority for the protection of the rights of native Papuans to be 'based on respect for the customs and culture,- women's empowennent, and stabilization of harmoniousreligious life. Recruitment process is based on traditional elements, religious elements,and the female element. Toobtain a picture of the institutional capacity of MRP as a representative institution natives of Papua,as the ob}ectives to be achieved in this study, ,the author~ use this type of qualitative researchmethods of interviews and documentation studies. Furthennore, to obtain the validity / validityof the data, then the analysis also uses a qualitative approach. This st'.:dy w:s conducted to answer the question, How Institutional Capacity of the PapuanPeople's Assembly? To answer these questions, theoretical framework is built include: MRP as a means of representation of indigenous people of Papua, institution, authority, recruitment,ethnicity, marginalization and MRP constraints in implementiiig the tasks and functions. The results of this study indicate, institutions Papuan People's Assembly (MRP) in carryingout the mandated duties and authorities there are some obstacles or barriers that are oftenencountered include: (a) The existence of half-hearted political attitude of the government, thus undermining the performance of the Papuan People's Assembly (MRP) , (b) There is suspicionof government (shadow separatism), (c) The recruitment process specific elements of customarynature of the selection of lower levels, so laden with political dinamics and the politicsof money, (d) Even the observer Papua issue, see the MRP, cultural institutions still gray, so that the institution established as a place that aims to fight for basic rights of indigenous peopleof Papua have not been properly empowered, (e) a very strong political intervention from thegovernment